Щодо дослідницьких пріоритетів у справі створення нового академічного синтезу української історії в контексті історії світової - Потульницький, В.А. (Український історичний журнал, 2014)
Викладено міркування з приводу необхідності написання нового академічного
синтезу історії України в контексті специфіки дослідження таких феноменів,
як державна й династична історії, а також кроків, що їх, на думку автора,
слід зробити на шляху інтеґрації української історії у світову. Подається аналіз династичних планів засновників українських спадкоємних гетьманатів – Б.Хмельницького (1649 р.) та П.Скоропадського (1918 р.). The article deals with the author’s vision about the necessity of making a new academic
synthesis of Ukrainian history in the framework of research of two another basic problems:
the specifics of the investigations of the state history, from the one side, and dynastic
history, from the another side; the concrete necessary steps, which can help to integrate
the own version of the country’s past in the world history. The article also includes
the analysis of the dynastic plans of creators of both Ukrainian hereditary het’manates,
founded accordingly by B.Khmel’nyts’kyi in 1649 and P.Skoropads’kyi in 1918.